Thecla Shiphorst: Development of wearable technology as a tool for expressive interaction - Cedrón, María Gutiérrez (Seven Editora, 2024)
Thecla Schiphorst builds her work by establishing links between art, body and tecnology. Through her consecutive interactive installations whisper: wearable body architecture (2001-2003) and exhale: (breath between bodies) (2003-2005) she uses wearable technology as an interface between the self and the inner self; between the self and the other; between the self and the environment. In this terrains of human/computer interaction with somatic and perfomative methodologies. DOI:https://doi.org/10.56238/sevened2024.010-056